Analisis Hadis Tentang Sumur Barhut dalam Perspektif Dakwah dan Sejarah Peradaban Islam - Nai’imah, Elvi; Fatchurrohman, Muhammad; Abbas, Ngatmin (MAMBA'UL 'ULUM, 2026)
This study is motivated by the widespread narratives about the Well of Barhut circulating in society without adequate hadith verification. The purpose of this research is to analyze the quality of hadiths related to the Well of Barhut and to understand their meanings from the perspectives of Islamic preaching and historical civilization. This research employs a qualitative approach using library research. Data were collected through documentation from hadith books, da’wah literature, and Islamic historical sources, then analyzed using hadith takhrij and content analysis methods. The findings indicate that the hadiths concerning the Well of Barhut are generally classified as weak (da‘if) due to deficiencies in their chains of transmission, thus they cannot be used as a basis for legal rulings. However, substantively, these hadiths contain moral messages that can be utilized in da’wah as symbolic warnings and reinforcement of Islamic values. From a historical perspective, the narrative of the Well of Barhut has evolved as part of the religious-cultural construction of Muslim society. The implication of this study highlights the importance of caution in using hadith for da’wah and the need for an integrative approach combining hadith studies, da’wah, and historical analysis.